The effects of age and ganglioside composition on the rate of motor nerve terminal regeneration following antibody‐mediated injury in mice. Issue 7 (14th March 2013) - Rupp, Angie; Cunningham, Madeleine E.; Yao, Denggao; Furukawa, Koichi; Willison, Hugh J.
ABSTRACT Gangliosides are glycosphingolipids highly enriched in neural plasma membranes, where they mediate a diverse range of functions and can act as targets for auto‐antibodies present in human immune‐mediated neuropathy sera. The ensuing autoimmune injury results in axonal and motor nerve terminal (mNT) degeneration. Both aging and ganglioside‐deficiency have been linked to impaired axonal regeneration. To assess the effects of age and ganglioside expression on mNT regeneration in an autoimmune injury paradigm, anti‐ganglioside antibodies and complement were applied to young adult and aged mice wildtype (WT) mice, mice deficient in either b‐ and c‐series (GD3sKO) or mice deficient in all complex gangliosides (GM2sKO). The extent of mNT injury and regeneration was assessed immediately or after 5 days, respectively. Depending on ganglioside expression and antibody‐specificity, either a selective mNT injury or a combined injury of mNTs and neuromuscular glial cells was elicited. Immediately after induction of the injury, between 1.5% and 11.8% of neuromuscular junctions (NMJs) in the young adult groups exhibited healthy mNTs. Five days later, most NMJs, regardless of age and strain, had recovered their mNTs. No significant differences could be observed between young and aged WT and GM2sKO mice; aged GD3sKO showed a mildly impaired rate of mNT regeneration when compared with their younger counterparts. Comparable rates were observed between all strains in the young and the aged mice. In summary, the rate of mNT regeneration following anti‐ganglioside antibody and complement‐mediated injury does not differ majorly between young adult and aged mice irrespective of the expression of particular gangliosides. Synapse 67:382–389, 2013. © 2013 Wiley Periodicals, Inc.